KEBIJAKAN PENANGGULANGAN KEJAHATAN TINDAK PIDANA TEKNOLOGI INFORMASI - Andhika Abdillah; Muhammad Muhtarom; Ismiyanto (LP3M, 2022)
Advances in science and technology have had a very positive impact on human civilization. One of the phenomena of the modern century which is still growing rapidly is the internet. The rapid development of technology requires legal arrangements related to the use of this technology. Unfortunately, until now many countries do not have specific legislation in the field of information technology, both in criminal and civil aspects. The existence of Electronic Information and/or Electronic Documents is binding and recognized as valid evidence to provide legal certainty for the Operation of Electronic Systems and Electronic Transactions, especially in evidence and matters related to legal actions carried out through Electronic Systems. In order to protect the public interest from all kinds of disturbances as a result of misuse of Electronic Information and Electronic Transactions, it is necessary to affirm the Government's role in preventing the dissemination of illegal content by taking action to terminate access to Electronic Information and/or Electronic Documents that have content that violates the law so that they cannot be accessed. from the jurisdiction of Indonesia and authority is required for investigators to request information contained in Electronic System Operators for the purposes of enforcing criminal law in the field of Information Technology and Electronic Transactions